(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the toponymy section of onomastics. Also, macro and micro toponyms included in the term-hyperony of toponymy are analyzed in detail on the basis of the territory of Konibodom district. The materials of this article can be used in toponymic research, in the creation of toponymic dictionaries